Livelihood Strategies And Livelihood System of Dryland Farmers - Nuryati, Rina; Faqihuddin, Faqihuddin; Permata Bunda, Cici Aulia (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
Dry land has great potential to support increased agricultural production, but its status is critical and farmers generally have weak capabilities (especially on capital). There is also a practice that destroys the environment and low technology adoption resulting in low income. Therefore, farmers are required to think rationally so that their needs are met through a livelihood strategy that is not limited to livelihoods but rather a livelihood strategy through the use of agricultural development capital. This research was conducted with the aim of knowing the livelihood strategies and livelihood systems of dry land farmers. The research method used a survey in two selected sub-districts, namely Cibalong and Karangnunggal, Tasikmalaya Regency, with a population of 3,684 dry land farmers, then the sample was taken by proportional simple random sampling, as many as 44 farmers from Parung Village, Cibalong Sub-District and 59 farmers from Cikupa Village, Karangnunggal Sub-District, so that the total sample is 103 people. The research was conducted from May to July 2023. Farmers' livelihood strategies were analyzed by the income and expenditure structure of farmer households and the purchasing power of farmers. Meanwhile, the farmer's livelihood system was analyzed descriptively in relation to the farmer's access to natural resource capital, economic capital, social capital, human capital and physical capital. The results showed that the strategy for fulfilling the needs of farmer households was carried out by seeking income from agriculture and non-agriculture. The average income of farmers from farming is IDR 17,793,227.18 per year and from non-agriculture is an average of IDR. 3,893,689.32 per year. So that the average total income of farmer households per year is IDR 21,686,916.50 or IDR 1,807,243.03 per month. Expenditures for farmer households IDR. 16,590,417.48 per year (for agricultural businesses IDR. 8,909,495.15 and for non-agricultural businesses IDR. 7,680,922.33 per year). As many as 36 percent of farming families are categorized as food insecure, while others are categorized as food secure. Based on the power value, all farming families are able to meet their expenses. The results of the analysis of farmers' livelihood systems related to capital factors (natural capital, economic capital, socio-cultural capital, human resource capital and infrastructure capital) are needed to support farmers' livelihood systems through sustainable Integrated Polyculture Plantation Farming (IPPF) management. 88.36 percent of respondents agreed and strongly agreed that natural capital is capital that supports farmers' livelihood systems through sustainable IPPF. Meanwhile, 70.10 percent agreed and strongly agreed that economic capital is capital that supports farmers' livelihood systems through sustainable IPPF management.